A note on the estimation of asset pricing models using simple regression betas - Raymond Kan; Cesare Robotti (Federal Reserve Bank of Atlanta, 2009)
Since Black, Jensen, and Scholes (1972) and Fama and MacBeth (1973), the two-pass cross-sectional regression (CSR) methodology has become the most popular tool for estimating and testing beta asset pricing models. In this paper, we focus on the case in which simple regression betas are used as regressors in the second-pass CSR. Under general distributional assumptions, we derive asymptotic standard errors of the risk premia estimates that are robust to model misspecification. When testing whether the beta risk of a given factor is priced, our misspecification robust standard error and the Jagannathan and Wang (1998) standard error (which is derived under the correctly specified model) can lead to different conclusions.
Keywords: G12; 330; two-pass cross-sectional regressions; risk premia; model misspecification; simple regression betas; multivariate betas